Multi-scale interactions of microtearing turbulence in the tokamak pedestal. (29th October 2020) - Pueschel, M.J.; Hatch, D.R.; Kotschenreuther, M.; Ishizawa, A.; Merlo, G.
Abstract: Microtearing turbulence in an idealized pedestal scenario is found to saturate via zonal fields, while also exciting strong zonal flows; a concurrent upshift of the non-linear critical gradient is observed. The zonal flows cause electron-temperature-gradient-driven turbulence to be ameliorated. When applying resonant magnetic perturbations, the prompt charge loss off the flux surface erodes the zonal flow, leading to higher electron-scale fluxes, while leaving microtearing saturation physics unaffected.